1996
DOI: 10.1590/s0101-81751996000200011
|View full text |Cite
|
Sign up to set email alerts
|

Eurytrema coelomaticum (Giard & Billet) (Digenea, Dicrocoeliidae) em Bradybaena similaris (Férussac) (Gastropoda, Xanthonychidae): alterações nos depósitos de cálcio e na função reprodutiva do primeiro hospedeiro intermediário

Abstract: (Férussac, 1821) was experimentally studied in infected and uninfected snail s maintained in laboratOlY under controlled conditions ofnutrition, humidity and temperature. The ca\cium ofthe shell s of infected and uninfected snail s was quantitled by using a technique of volumetric complexation. The amount of calciull1 present in the tissue was evaluated by using the histochemistry techniques of Dahl and von Kossa. The alteration in the reproductive I'unction was evaluated through the egg production, and by hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It has been demonstrated that in male H. parchappii, the infestation of certain digenea may produce a decrease in the size of the penis (Merlo et al 2017). These alterations in H. parchappii had also been observed in Biomphalaria glabrata (Say, 1818), Bradybaena similaris (Férussac, 1821), Chilina dombeyana (Bruguière, 1789), and Hydrobia ventrosa (Montagu, 1803;Théron & Gérard, 1994;Paschoal & Amato, 1996;Olmos & George-Nascimento, 1997;Kube et al 2006;Valdovinos & Balboa 2008, Horak & Kolarova, 2011.…”
Section: Discussionmentioning
confidence: 92%
“…It has been demonstrated that in male H. parchappii, the infestation of certain digenea may produce a decrease in the size of the penis (Merlo et al 2017). These alterations in H. parchappii had also been observed in Biomphalaria glabrata (Say, 1818), Bradybaena similaris (Férussac, 1821), Chilina dombeyana (Bruguière, 1789), and Hydrobia ventrosa (Montagu, 1803;Théron & Gérard, 1994;Paschoal & Amato, 1996;Olmos & George-Nascimento, 1997;Kube et al 2006;Valdovinos & Balboa 2008, Horak & Kolarova, 2011.…”
Section: Discussionmentioning
confidence: 92%
“…This pathology is well documented for many Gastropoda species (e.g. Wilson & Denilson 1980;Paschoal & Amato, 1996;Jordaens et al, 2007;Voutilainen et al, 2009;Averbuj & Cremonte, 2010).…”
Section: Omalonyx Geayi Tillier 1980mentioning
confidence: 86%
“…Travassos (1928) subsequently used specimens of Omalonyx from Mato Grosso, Brazil as experimental host for this trematode which develops in the slug's visceral cavity, but does not infest host organs. Montresor et al (2008) (Robinson, 1953;Rowan, 1955;Paschoal & Amato, 1995, 1996, 2001. Unfortunately, our Omalonyx material was preserved in alcohol and not suitable for determination of the family or specific identity of the parasites infecting the gonad and hermaphrodite duct.…”
Section: Omalonyx Geayi Tillier 1980mentioning
confidence: 99%
“…When the results were expressed in ppm of CaCO 3 /mg of shell, wet weight, according Pinheiro and Amato (1995), the presence of organic matter may give us an erroneous interpretation because they not reflects directly the calcium alterations in the shell. Paschoal and Amato (1996) observed that in B. similaris infected with Eurytrema coelomaticum (Giard et Billet, 1892) the weight of the shell increases, but the calcium amount is reduced. So, Pinheiro and Amato (1995) technique must be masked and the results may not express the alterations in the calcium content in the shell, but they may be masked by the increase in the organic matter in the shell.…”
Section: Discussionmentioning
confidence: 99%
“…Many physiological alterations may affect the calcium reserves in the shell and in the hemolymph of mollusks (Souza et al, 2000;Lira et al, 2000;Pinheiro, 1996). Calcium determination in the shell of the snails is an important parameter that is widely used as an indirect evaluation of metabolic alterations, influence of the environment and conditions of stress on the physiology of molluscs (Paschoal and Amato, 1996;Brandolini and Amato, 2001;Moreira et al, 2003). The calcium present in the shell is predominantly found as calcium carbonate incorporated in the shell structure as calcite and aragonite crystals associated to the organic matrix, composed basically by conchiolin.…”
Section: Introductionmentioning
confidence: 99%